2020
DOI: 10.1002/ags3.12312
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab‐associated intestinal perforation and perioperative complications in patients receiving bevacizumab

Abstract: Aim The purposes of this study are to present cases of emergency surgery in which gastrointestinal perforation occurred during bevacizumab administration, consider the indications for emergency surgery, and examine the safety of scheduled surgery after a washout period for bevacizumab. Methods (a) We retrospectively investigated seven patients who underwent emergency surgery for bevacizumab‐associated intestinal perforation. (b) We investigated 104 patients with advanced colorectal cancer treated with neoadjuv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
(102 reference statements)
0
10
0
Order By: Relevance
“…BVZ, the most commonly used VEGFA inhibitor, is an effective anti‐angiogenic agent that has been proven to delay the progression of tumours in patients 22,23 . However, BVZ treatment may lead to microvascular damage, resulting in cardiovascular disease, thromboembolic events, and gastrointestinal perforation, 24–26 suggesting that BVZ induced cardiotoxicity may also be caused by endothelial cell damage. In addition, Previous studies reported that myocardial ischaemia is a potential life‐threatening and not uncommon complication of 5‐fluorouracil or capecitabine chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…BVZ, the most commonly used VEGFA inhibitor, is an effective anti‐angiogenic agent that has been proven to delay the progression of tumours in patients 22,23 . However, BVZ treatment may lead to microvascular damage, resulting in cardiovascular disease, thromboembolic events, and gastrointestinal perforation, 24–26 suggesting that BVZ induced cardiotoxicity may also be caused by endothelial cell damage. In addition, Previous studies reported that myocardial ischaemia is a potential life‐threatening and not uncommon complication of 5‐fluorouracil or capecitabine chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed that there was no statistical difference in the risk of GIP between VEGFRtyrosine kinase inhibitors (TKIs) and control groups (28). However, cases of GIP caused by anti-VEGF/VEGFR agents have been continuously reported in recent years (29)(30)(31). Wang Z et al found that ramucirumab, a novel anticancer drug that belongs to the class of anti-VEGF agents, is associated with a significant increase in the risk of GIP (32).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Badgwell and others identified 24 patients with gastrointestinal perforation following treatment with bevacizumab and reported a 30-day mortality rate of 12.5%—in contrast to the 36% mortality rate reported here [ 17 ]. Another study reported that operative management of gastrointestinal perforation after bevacizumab yielded short-term mortality in 2 of 7 patients [ 18 ]. Three factors may explain the higher mortality reported in the current study.…”
Section: Discussionmentioning
confidence: 99%